2022
DOI: 10.3389/fchem.2022.898436
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Apoptosis-Promoting Effect Evaluation of Rhopaladins’ Analog 4-Arylidene-5-Oxopyrrolidine Derivatives

Abstract: Marine alkaloids have novel structures and antitumor activities. Therefore, we synthesized rhopaladins’ analogs from marine alkaloids rhopaladins A-D and modified their structures to synthesize 4-benzylidene-5-pyrrolidone derivatives. Among the compounds, (2E, 4E)-4-(4-chlorobenzylidene)-2-(4-chlorostyryl)-N-cyclohexyl-1-(4-fluorophenyl)-5-oxopyrrolidine-2-carboxamide (RPDPRH) has high efficiency and less hepatotoxicity, with IC50 values of 4.66, 6.42, 17.66, 15.2, 12.36, 22.4, and 243.2 μM in vitro anti-proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The synthesis procedure was based on our previous research ( Zhu et al, 2022 ). First, a mixture of 4-fluoroaniline 2 (1 mmol) and substituted ( E )-3-(4-chlorophenyl) acrylaldehyde 3 (1 mmol) was stirred in ethanol-water (3:1, vol/vol, 8 ml) at room temperature for 30 min.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis procedure was based on our previous research ( Zhu et al, 2022 ). First, a mixture of 4-fluoroaniline 2 (1 mmol) and substituted ( E )-3-(4-chlorophenyl) acrylaldehyde 3 (1 mmol) was stirred in ethanol-water (3:1, vol/vol, 8 ml) at room temperature for 30 min.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Following previous studies ( Zhu et al, 2022 ), cell activity was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT, MultiSciences) assay. The logarithmic growth phase cells were digested and inoculated into 96 well cell culture plates with 5 × 10 3 cells per well.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies have shown that marine alkaloids rhopaladins A–D have significant cytotoxicity to human tumor cell lines. Rhopaladin B has inhibitory activity against CDK4 and c-erbB-2 kinases (IC 50 of 12.5 and 7.4 μg/ml, respectively) ( Hiroyasu et al, 1998 ; Zhu et al, 2019 .). We have previously synthesized rhopaladins’ analogs 2-aroyl-4-arylidene-5-oxopyrrolidine derivatives (see Scheme 1 ) via a tandem Ugi 4CC/S N cyclization and studied their cytotoxicity to HeLa cells ( Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that rhopaladins A-D alkaloids (Janosik et al, 2002;Méndez et al, 2018) (Scheme 1) present in marine cysts have significantly biological activities. We have previously synthesized several different series of rhopaladins' analogs, such as (E)-2-aroyl-4-arylidene-5-oxopyrrolidines (Scheme 1), and (2E, 4E)-2-styryl-4-arylidene-5-oxopyrrolidines, via multi-component one-pot method starting from Baylis-Hillman acid, and found that these compounds showed good anti-proliferation and apoptosis-inducing effects on cervical cancer cells and liver cancer cells, respectively (Zeng et al, 2013;Zhu et al, 2020;Wang et al, 2021;Wang et al, 2021;Kong et al, 2021;Zhu et al, 2022). Baylis Hillman (B-H) reaction is a coupling reaction between active alkenes and electrophiles under catalyst, which can be used to synthesize compounds with polyfunctional groups under mild reaction conditions (Huang and Cui, 2018).…”
Section: Introductionmentioning
confidence: 99%